Glycyrrhetinic acid nanoparticles combined with ferrotherapy for improved cancer immunotherapy. (May 2022) - Li, Qing; Su, Rui; Bao, Xin; Cao, Kunxia; Du, Yangyang; Wang, Nanya; Wang, Jianfeng; Xing, Fan; Yan, Fei; Huang, Keke; Feng, Shouhua
Abstract: Programmed cell death protein 1 (PD-1)/Programmed Cell Death Ligand 1 (PD-L1) blockade immunotherapy has emerged as a promising strategy to treat both solid and hematological malignancies. Despite the considerable therapeutic effects obtained in pre-clinical and clinical studies, PD-1/PD-L1 blockade therapy is still limited by the low benefit rates and a large number of patients still do not respond to this treatment. In this study, we developed a highly efficient and cancer-specific immunogenic cell death nanoinducer for effective tumor immunotherapy. A leukocyte membrane coated poly (lactic-co-glycolic acid) encapsulating glycyrrhetinic acid (GCMNPs) was developed to enhance targeting, tumor-homing capacity, and reduce toxicity in vivo. GCMNPs could induce ferroptosis in acute myeloid leukemia and colorectal cancer cells by downregulating glutathione-dependent peroxidases 4, leading to increased lipid peroxidation levels. Moreover, GCMNPs and ferumoxytol could synergistically enhance Fe-dependent cytotoxicity through the Fenton reaction. Finally, in vivo studies showed that GCMNPs synergized with ferumoxytol and anti-PD-L1 synergistically improve T-cell immune response against leukemia and colorectal tumor. This study anticipated that the combination of glycyrrhetinic acid-based nanomaterials and ferrotherapy would provide further insights into anti-cancer immune response to PD-1/PD-L1 blockade for both solid and hematological malignancies. Statement of significance: Despite the considerable therapeutic effects obtained in pre-clinical and clinical studies, PD-1/PD-L1 blockade therapy is still limited by the low benefit rates and a large number of patients still do not respond to this treatment. We designed a glycyrrhetinic acid-based nanoplatform as a new ICD inducer (GCMNPs), with high cancer cell specificity and reduced toxicity to AML and CRC. GCMNPs cooperates with ferumoxytol to promote a Fenton reaction and induce ferroptosis. Moreover, the combination of GCMNPs and ferumoxytol enhanced the blockage of PD-1/PD-L1 to activate T cells, subsequently generating a systemic immune response in CRC and AML mouse models. This pre-clinical findings provide the proof-of-concept of combination of glycyrrhetinic acid-based nanomaterials and ferrotherapy as an "ICD nano-inducer" and immunotherapeutic agent for treating cancer. Graphical abstract: Image, graphical abstract